Targeting Bruton’s Tyrosine Kinase in CLL - Ahn, Inhye E.; Brown, Jennifer R. (Frontiers in Immunology, 2021)
Targeting the B-cell receptor signaling pathway through BTK inhibition proved to be effective for the treatment of chronic lymphocytic leukemia (CLL) and other B-cell lymphomas. Covalent BTK inhibitors (BTKis) led to an unprecedented improvement in outcome in CLL, in particular for high-risk subgroups with TP53 aberration and unmutated immunoglobulin heavy-chain variable-region gene. Ibrutinib and acalabrutinib are approved by the US Food and Drug Administration for the treatment of CLL and other B-cell lymphomas, and zanubrutinib, for patients with mantle cell lymphoma. Distinct target selectivity of individual BTKis confer differences in target-mediated as well as off-target adverse effects. Disease progression on covalent BTKis, driven by histologic transformation or selective expansion of BTK and PLCG2 mutated CLL clones, remains a major challenge in the field. Fixed duration combination regimens and reversible BTKis with non-covalent binding chemistry hold promise for the prevention and treatment of BTKi-resistant disease.